TWO MODES OF DEGRADATION OF THE TRAMTRACK TRANSCRIPTION FACTORS BY SIAH HOMOLOGUES - Cooper, Sarah E. (2007)
The Siah proteins, mammalian homologues of the Drosophila Sina protein, function as E3 ubiquitin ligase enzymes to target a wide range of cellular proteins for degradation. We report here a novel Drosophila protein that is homologous to Sina, named Sina-Homologue (SinaH). We show that it can direct the degradation of the transcriptional repressor Tramtrack (Ttk), using two different mechanisms. One is similar to Sina and requires the adaptor Phyllopod, and the other is a novel mechanism of recognition. This novel mode of targeting for degradation is specific for the Ttk isoform, Ttk69. Ttk69 contains a region that is required for binding of SinaH and for SinaH directed degradation. This region contains an AxVxP motif, which is the consensus sequence found in Siah substrate proteins. These results suggest that degradation directed by SinaH differs from that directed by Sina and is more similar to that found in vertebrates. We speculate that SinaH may be involved in regulating the levels of developmentally important transcription factors.